Perceptions, attitudes, and experiences of domestic violence among Vietnamese university students - Dang-Quang Le; Ha-An Nguyen; Dan-Tam Pham Nguyen; Ngan P. Nguyen (SSM - Mental Health)
Background: In Vietnam, domestic violence (DV) is recognized as an intentional act of causing physical, mental, sexual, or economic harm among family members. Despite legislative efforts, DV remains prevalent, significantly impacting women's mental and physical health. Traditional beliefs and cultural norms further entrench DV, particularly among women and children, necessitating an understanding of perceptions and attitudes toward DV. Methods: This exploratory cross-sectional study surveyed 81 Vietnamese university students to assess their perceptions, attitudes, and personal experiences of DV. Survey data was collected online and analyzed using descriptive statistics. Results: The study found high awareness of DV, with most participants recognizing physical and psychological violence, while less awareness was noted for economic abuse. A majority perceived DV as fairly common (57%) and highly common (37%). Most participants attributed DV to alcoholism (93%), drug addiction (93%), and poverty or social exclusion (90%). Roughly half of the participants had friends or family victims who were victims (53%) or perpetrators (46%) of DV. Despite general knowledge of DV laws, many were unaware of specific legal and social support mechanisms. Notably, while most participants found DV unacceptable and should always be punishable by law (64%), actual reporting and intervention rates were low, with significant gaps in support awareness. Conclusions: The findings highlight a substantial awareness of DV among Vietnamese university students but also reveal critical gaps in understanding and addressing economic abuse and available support systems. There is a need for enhanced education and accessibility of resources to effectively combat DV and support survivors, especially for young adults who would soon explore marriage and family lives.